TEACHING WRITING RECOUNT TEXT USING RECEIPTS AS MEDIA OF THE EIGHTH GRADE STUDENTS - wahyuni wahyuni; Sulistyaningsih (STKIP PGRI SIDOARJO, 2020)
This study was purposed to describe the implementaion of teaching writing recount text by using receipts and to describe students’ cognitive responds in writing recount text by using receipts as media. This study was quantitative research and used experimental method. The quasi experimental was used as the research design and test was the instrument. The students of the eighth grade of SMP Negeri 5 Sidoarjo were as the sample. The number of students in this study was 66 people that 33 people were experimental class students and 33 people were as controlled class students. The SPSS 20 was used to calculate the data. It was proven that sig.2 tailed (p) was for the test of hypothesis proved that sig. 2 tailed (p) was 0.049 while alpha (α) was 0.05. In other words, p < α. It meant that the Ho (Null Hypothesis) was denied and Ha (Alternative Hypothesis) was allowed. It was proven that it had a positive effect of using receipts to students’ writing skill of recount text. Moreover, the result of Cohen’s formulation calculation proved the effect size of receipts result was 0.49. It can be concluded that the effect of this treatment was modest effect.